2011
DOI: 10.1136/thx.2010.152801
|View full text |Cite
|
Sign up to set email alerts
|

A simplified model of screening questionnaire and home monitoring for obstructive sleep apnoea in primary care

Abstract: Background To address the growing burden of disease and long waiting lists for sleep services, a simplified twostage model was developed and validated for identifying obstructive sleep apnoea (OSA) in primary care using a screening questionnaire followed by home sleep monitoring. Methods 157 patients aged 25e70 years attending their primary care physician for any reason at six primary care clinics in rural and metropolitan regions of South Australia participated. The first 79 patients formed the development gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
4
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(184 citation statements)
references
References 37 publications
3
170
4
7
Order By: Relevance
“…The formulation of these recommendation statements was guided by evidence from twenty-six validation studies that evaluated the diagnostic accuracy of HSAT against PSG, 35,53,62,67,81, as well as seven RCTs that compared clinical outcomes from management pathways. [83][84][85][107][108][109][110] Four of these RCTs were determined to be most relevant to clinical practice, as they did not require oximetry testing as a criterion for inclusion and used conventional methods for determination of PAP pressures (i.e., APAP or attended titration).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The formulation of these recommendation statements was guided by evidence from twenty-six validation studies that evaluated the diagnostic accuracy of HSAT against PSG, 35,53,62,67,81, as well as seven RCTs that compared clinical outcomes from management pathways. [83][84][85][107][108][109][110] Four of these RCTs were determined to be most relevant to clinical practice, as they did not require oximetry testing as a criterion for inclusion and used conventional methods for determination of PAP pressures (i.e., APAP or attended titration).…”
Section: Discussionmentioning
confidence: 99%
“…The OSA50 questionnaire involves four components including age ≥ 50, snoring, witnessed apneas and waist circumference. 81 A study involving Turkish bus drivers 82 and a validation study for the OSA50 in the primary care setting 81 showed a sensitivity ranging from 0.49-0.98 and a specificity of 0.82 in both studies (see supplemental material, Table S32 and Table S33). …”
Section: Multivariable Apnea Prediction Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The mean nocturnal SaO 2 (<SaO2>) and SaO 2 nadir were registered. Since ApneaLink does not differentiate between central or obstructive respiratory events, mild SDB was diagnosed in the presence of an ODI between 2 and 5 and severe SDB was defined by an ODI of ≥5 (15,16,18).…”
Section: Sleep Assessmentmentioning
confidence: 99%
“…Sleep assessment was performed using a portable device (ApneaLink, ResMed, Basel, Switzerland; refs [15][16][17], at baseline and after 4-6 months of therapy when SDB was observed during the first investigation. Respiratory airflow was measured by a nasal pressure cannula (detecting −10 hPa to +10 hPa) and oxygen saturation (SaO 2 ) and pulse rate were obtained by using a pulse oxymeter and a pulse sensor (sampling rate of 1 Hz).…”
Section: Sleep Assessmentmentioning
confidence: 99%